A Review On. Current Climate Changes Are Forerunners Of Major Changes In Living Creatures In The Future (International Journal of Food and Nutritional Sciences, 2022)
Human activities, such as urbanization, deforestation, and agriculture, alter the landscape, leading to changes in land use and land cover. Overexploitation of natural resources, such as overfishing, deforestation, and excessive extraction of minerals, can lead to the degradation of ecosystems and the loss of biodiversity. Natural events like wildfires, disease outbreaks, and invasive species can disturb ecosystems, impacting their structure and function. Pollution from various sources, including industrial activities, agriculture, and waste disposal, can contaminate air, water, and soil, harming both human and ecosystem Climate change amplifies the impacts of these stressors, leading to more severe and widespread consequences for ecosystems. Ecosystems already under stress are likely to respond more rapidly and acutely to the added pressure of climate change, potentially leading to tipping points or irreversible changes. Recognizing the interconnectedness of environmental stressors is vital for developing comprehensive and effective climate adaptation strategies.